Numerical study of a wake-stabilized propane flame in a cross-flow of air. Issue 1 (February 2017) - Aboje, Alechenu A.; Hughes, Kevin J.; Ingham, Derek B.; Ma, Lin; Williams, Alan; Pourkashanian, Mohamed
Abstract: Predictions of flame structures, flame temperatures, and species concentrations have been numerically performed for a wake-stabilized propane flame in a cross-flow of air. The flow field has been modeled using the Reynolds-Averaged Navier-Stokes equation incorporating the Reynolds Stress turbulence closure Model (RSM) and the Large Eddy Simulation (LES) technique with the two methods compared. The combustion processes were modeled using the partially premixed and the non-premixed models and the two sets of results have also been compared. The CRECK reaction mechanism was used to model the kinetics of the propane reactions while soot in the flame was modeled with the Moss-Brookes-Hall model. Thermal radiation in the flame was modeled with the discrete ordinate method. The results of the simulation have been validated against experimental data and show that the partially premixed model performs better than the non-premixed model for wake-stabilized flames that are attached to the lee-side of the flare burner. Furthermore, the LES technique has been shown to perform better than the RSM. Highlights: For a wake-stabilized propane flame in a cross-flow of air, the partially premixed combustion model is preferred. The Large eddy simulation method works better than the Reynolds stress model for resolving the turbulence in the flow field. The CRECK reaction mechanism and Moss-Brookes-Hall soot model successfully predicted the structure of the flame.